Percepatan Akuntabilitas BUMDesa di Kabupaten Temanggung Lewat ToT Penyusunan Laporan Keuangan - Akhmad Solikin; Akhmad Priharjanto; Imam Subroto (Penerbit Goodwood, 2025)
Purpose: The accountability of village-owned enterprises (BUMDesa) is important since their capitals are from village governments and/or communities. This community development program aims at accelerating accountability of village-owned enterprise in Temanggung Regency by enhancing capacities to prepare financial reports. Methodology/approach: Training of Trainers for BUMDesa staffs and Village Mentors was taking place in Temanggung Regency, Jawa Tengah Province. The training was followed by workshop to prepare financial reports using real BUMDesa data. Monitoring and mentoring via online meeting and chat group were also be provided. Results/findings: The training succeeded to enhance participants’ knowledge in preparing financial reports using Excel application. Several participants also reported their activities to share their knowledge in financial reporting and business development. Conclusions: The community service activity described in this article successfully achieved its objectives by enhancing the accountability of Village-Owned Enterprises (BUMDesa). This was accomplished through improving the capacity of administrators and Village Companions to prepare accurate and accountable financial reports, thereby supporting better transparency and governance. Limitations: Limited funding restricts the implementation of offline mentoring to the locations of the training participants, thereby limiting the frequency and scope of direct assistance and follow-up support. Contribution: This community development program exhibits successful implementation of a program to enhance accountability of village-owned enterprise by training, mentoring, and monitoring in preparing of financial reports.